Da poesia de intervenção ao signo erótico-amoroso : alteridade e subjetividade na poesia de Carlos Drummond de Andrade e de José Craveirinha - Rego, Angela Cristina de Souza (2008)
This paper suggests the understanding of alterity and subjectivity process in Carlos Drummond de Andrade and José Craveirinha s poetry. The purpose of this paper is to investigate how the "ego" is replaced by the other , in order to build a poetry defined as intervention poetry or revolutionary poetry and, conversely, how we can connect the themes and sign selected by the author to the subjective process. To put it another way, we try to recognize the subjectivity that outlines the erotic and love poem produced by these two poetic voices. The theoretical understanding is based on, to the alterity investigation, in the building of realistic poetry, resulting from the mimetic process acquires new contents and format from XIX century and in the Philosophy of Language depending on Marxist Ideology. Regarding the erotic and love subjectivity, it is suggested the research building based on theories prepared for the love and erotic body investigation, both founding in the oneself return proposal shown in the poems by Drummond and Craveirinha after the realism movement to which they dedicate most part of their lives.